The Influence of Livewire Learning on Vocational School Students’ Understanding and Psychomotor on Dynamic Electricity Subject Matter - Sukirman, Sukirman; Nugroho, Sunyoto Eko; Subali, Bambang (Universitas Negeri Semarang, 2024)
The aim of this research was to know the influence of the use of Livewire learning media and psychomotor for Light Vehicle Engineering Students on Dynamic Electricity Topic. This research used two group pretest-posttest method in which the object of the research divided into experimental group and control group consist of two different schools with the same major. An nN-gain analysis was used to calculate students’ understanding on dynamic electricity. The results of the n-gain calculations showed two scores for experimental group and control group where the experimental group gained 0.51 and 0.34, meanwhile the control group gained 0.34 and 0.31. Nevertheless, both experimental groups as well as the control group considered as medium level. Based on the results of students’ psychomotor in practicing (arranging) using livewire, the first experimental group gained a score of 74.16%, higher than the second experimental group that gained a total score of 73.10%, both in medium level. It can be concluded that N-gain score of the experimental group is higher than the control group. Along with that, the first experimental group had a higher score on psychomotor skills than the control group.